2005
DOI: 10.1148/radiol.2361041618
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate Ovarian Mass at US: Incremental Value of Second Imaging Test for Characterization—Meta-Analysis and Bayesian Analysis

Abstract: In women with an indeterminate ovarian mass at gray-scale US, MR imaging results contributed to change in probability of ovarian cancer in both pre- and postmenopausal women more than did CT or combined gray-scale and Doppler US results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(107 citation statements)
references
References 39 publications
4
95
0
8
Order By: Relevance
“…The values of sensitivity and specificity of MDCT in differentiation of ovarian masses are comparable to those reported in literature (Kinkel et al, 2005;Gatreh-Samani et al, 2011). A sensitivity and specificity of 81% and 87% has been reported by Kinkel et al (2005) in their Meta-analysis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The values of sensitivity and specificity of MDCT in differentiation of ovarian masses are comparable to those reported in literature (Kinkel et al, 2005;Gatreh-Samani et al, 2011). A sensitivity and specificity of 81% and 87% has been reported by Kinkel et al (2005) in their Meta-analysis.…”
Section: Discussionsupporting
confidence: 85%
“…A sensitivity and specificity of 81% and 87% has been reported by Kinkel et al (2005) in their Meta-analysis. Similarly Tsili et al have reported that MDCT can categorize adnexal masses into benign and malignant with a sensitivity and specificity of up to 90.5% and 93.7% respectively.…”
Section: Discussionmentioning
confidence: 87%
“…This showed that in women with an indeterminate ovarian mass at gray-scale US, MR imaging findings contributed to a change in probability of ovarian cancer in both pre-and post-menopausal women more than did CT or combined gray-scale and Doppler US results [12] . Furthermore, in a prospective multi-centre study of 143 patients with a pelvic mass, where diagnostic uncertainty existed, MRI improved diagnostic accuracy, when judged by an expert radiologist [13] .…”
Section: S120 Focus On: Women S Imagingmentioning
confidence: 94%
“…The value of adding CT or MRI to ultrasound imaging in 'indeterminate ovarian masses' was studied in a meta-analysis. The results showed that MRI was superior to CT [137]. In another study, MRI was found to be superior to ultrasound for discriminating between benign and malignant adnexal masses, because it was associated with fewer false positive results [138].…”
Section: Palpable Pelvic Massmentioning
confidence: 94%